The effect of nursing students' perceptions of ARCS motivational teaching on their academic self-efficacy and attitudes towards learning: A structural equation modeling - Karabatak, Songul; Turan, Gulcan Bahcecioglu; Alanoglu, Muslim (Churchill Livingstone, 2023)
Background: Nursing education is a curriculum that assists individuals to manage nursing practices in health, illness, and rehabilitation processes. The curriculum aims to train nurses who will work in healthcare systems. Objective: This study was conducted to examine the effect of the perception of Attention, Relevance, Confidence, and Satisfaction (ARCS) motivation-based teaching method on attitudes and academic self-efficacy of nursing students towards learning. Design: A cross-sectional, correlational study. Settings: This study was performed in the nursing department of a state university located in Elazig in the east of Turkiye. Participants: A total sample of nursing students (n = 344). Methods: Data were collected using a personal information form, ARCS motivation theory-based teaching scale, academic self-efficacy scale and attitude towards learning scale. Results: According to the research model, it was found that the perception of teaching with ARCS motivation positively and significantly affected the academic self-efficacy (beta = 0.301) and attitudes towards learning (beta = 0.242) of nursing students. In addition, their academic self-efficacy also had a positive and significant effect on their attitudes towards learning (beta = 0.289). The indirect effect of the perception of teaching with ARCS motivation on students' attitudes towards learning through their academic self-efficacy (beta = 0.087) was found to be positive and significant. The total effect of perception of teaching with ARCS motivation method on nursing students' attitudes towards learning (beta = 0.329) was found to be positive and significant. In the model, the perception of teaching with ARCS motivation method was found to explain 9 % of students' academic self-efficacy and the total of the model was found to explain 18 % of students' attitudes towards learning. Model fit indices values have been detected as; chi(2)/df = 2.16, RMSEA = 0.058, SRMR = 0.080, CFI = 0.821 and TLI = 0.814. Conclusions: It is seen that the perception of teaching with ARCS motivation supports the attitudes of nursing students towards learning. Moreover, it also shows that teaching with ARCS motivation positively affects the attitudes of students towards learning through their level of self-efficacy.
Keywords: ARCS model; Academic self-efficacy; Attitude towards learning; Nursing student